THEORETICAL BASIS OF THE FORMATION OF FINANCIAL RESULTS IN THE COTTON-TEXTILE CLUSTER - Abdurashidova Guzal Akrom kizi (Scholar Express Journals, 2024)
The theoretical basis of the formation of financial results in the cottontextile cluster is considered. The process of origination of income and expenses from enterprise activity has been studied. The trends of the added value chain in cotton-textile clusters and the level of coverage of the added value chain in cotton-textile clusters operating in Uzbekistan were analyzed.
Keywords: Cotton-textile cluster; financial statement; profit and loss; economic entity